The Effectiveness of Group Guidance Service Through Techniques Games to Increase Student Empathy - Syari Fitrah Rayaginansih; Siti Nurhasanah SM; Siti Cahyati; Vina Dartina (Journal of Education and Counseling (JECO), 2023)
The ability to empathize is the ability to understand, have tolerance, and pay attention to others to avoid violent, cruel, or criminal behavior. This study aims to obtain empirical data and determine the effectiveness of group counseling services through game techniques to increase the empathy of class X students at Juang Kencana Health Vocational School, Sukabumi. This type of research uses a quasi-experimental method with a nonequivalent control group research design. Sampling technique using simple random sampling. The population is 57 students. Samples were obtained through pretest results. The results of the pretest researchers took 50 people as research subjects. Subjects were divided into two groups: 25 were the experimental group, and 25 were the control group. The data collection technique uses a research instrument in the form of a questionnaire. The number of empathy questionnaires is 60 items. Twenty-one items are invalid, and the remaining 39 will be distributed to respondents. Analysis techniques using t-test analysis. Based on the t-test results, tcount = 8,15 table = 2,110 with a significant level of ? =0,05 and dk=n-1 (25-1=24). From the study results, it can be seen that count? table. So the null hypothesis (Ho), which states “group guidance using game techniques is not effective for increasing the empathy of class X student at Juang Kencana Health Vocational School Sukabumi,” was rejected. While the alternative hypothesis (Ha) states that “group guidance through game techniques is effective for increasing the empathy of class X students at Juang Kencana Health Vocational School Sukabumi” is Accepted. As for recommendations for future researchers, it is hoped that they can use appropriate and more varied techniques, such as the socio-drama technique